Looking at the Margins: Is Inclusive Education for All? - Maria Antonietta Chieppa; Roberto Sánchez Cabrero; Marta Sandoval (MDPI AG, 2023)
Over the last 30 years, international education policies have emphasised the need for more inclusive environments, especially for previously marginalised and excluded populations. This article explores the status of culturally and linguistically diverse students with special educational needs in Spain between 2009 and 2019. Disaggregating the data by gender and origin (Spanish, EU, and non-EU), we compare the relative risk ratio (RRI) of ending up in a special education pathway for each group and relate it to the poverty risk index. The results reveal that male students from non-European backgrounds are more likely to attend a special school and that poverty has a different impact on the schooling of students depending on their origin. Therefore, while all Spanish laws support the rights-based anti-discrimination principle of equitable education, international and national policy objectives do not appear to be confirmed by educational practices. We conclude that the findings indicate a Eurocentric perspective that reads 'difference' as a form of deficit and propose to begin to question the role that colonial culture can play in developing inclusive policies and practices.